1985
DOI: 10.1172/jci111744
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil elastase modulates platelet function by limited proteolysis of membrane glycoproteins.

Abstract: During blood coagulation human polymorphonuclear leukocytes release elastase in amounts that can exceed 100 nmol/liter. We therefore studied the effect of elastase on platelet structure and function. Physiologic concentrations of elastase specifically inhibited thrombin-induced platelet aggregation and ristocetininduced agglutination of washed platelets in a time-and dosedependent manner. This was associated with a decrease in the number of high affinity thrombin binding sites on the platelet surface (analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 64 publications
5
51
0
Order By: Relevance
“…Proteolysis of platelet surface glycoproteins, in vivo, has been associated with cirrhosis of the liver (36). After the studies reported here were completed, Brower et al (37) have reported that platelets treated with human neutrophil elastase lose the ability to aggregate in response to thrombin and ristocetin. However, spontaneous aggregation to added fibrinogen was not tested by Brower et al (37).…”
Section: Discussionmentioning
confidence: 76%
“…Proteolysis of platelet surface glycoproteins, in vivo, has been associated with cirrhosis of the liver (36). After the studies reported here were completed, Brower et al (37) have reported that platelets treated with human neutrophil elastase lose the ability to aggregate in response to thrombin and ristocetin. However, spontaneous aggregation to added fibrinogen was not tested by Brower et al (37).…”
Section: Discussionmentioning
confidence: 76%
“…[29][30][31] Like thrombin, CG potently stimulates platelet aggregation through structurally related proteaseactivated receptors. 32,33 Although NE2 does not activate platelets by itself, [34][35][36][37] it significantly enhances the platelet aggregating property of CG, especially at lower concentrations. 30 CG and NE2 can proteolytically cleave the integrin ␣ IIb ␤ 3 , the mediator of platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…The complexities involved in studying effects of neutrophils on platelets are emphasized by recent contradictory reports in the literature. These range from neutrophil promotion of platelet reactivity (2)(3)(4)(5) to neutrophil blockage of platelet responsiveness (6)(7)(8)(9)(10)(11)(12). The reasons for these differences are not completely understood, but must in part be attributable to methodology.…”
Section: Introductionmentioning
confidence: 99%